Arising role of photovoltaic and wind energy in the power sector and beyond: Changing the Northeast Asian power landscape. (17th July 2018) - Bogdanov, Dmitrii; Farfan, Javier; Sadovskaia, Kristina; Fasihi, Mahdi; Child, Michael; Breyer, Christian
Abstract: Accordingly to the COP21 Paris Agreement a net zero greenhouse gas emission energy system must be built no later than 2050. Such a fast power system transition will be very challenging for the conditions of Northeast Asia, a region with a large and fast growing power demand. Power system transition modelling was performed in order to check the technical feasibility of such a transition. The results of the simulation show that the transition can be accomplished and a 100% renewable energy system is both technically feasible and economically viable in Northeast Asia with average electricity generation cost of around 55 €/MWh. Solar photovoltaic (PV) will become the major energy source in Northeast Asia with a generation share of more than 70%; wind energy will contribute to 18% of the generation. Decarbonisation of the system can be achieved quite fast: by 2035 CO2eq emissions in the power sector will decrease by 95 and 99% by 2045, respectively.